2018
DOI: 10.1039/c7nj04200k
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical fabrication of shape-controlled Cu2O with spheres, octahedrons and truncated octahedrons and their electrocatalysis for ORR

Abstract: Morphology-controlled synthesis of Cu2O is achieved by potentiostatic electrodeposition and it is used as an electrocatalyst for the oxygen reduction reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 41 publications
1
26
0
Order By: Relevance
“…The electron transfer number of Cu@Cu 2 O core-shell nanocatalyst estimated from the slope of the K–L plots is averagely 3.97 at 0.45–0.7 V, suggested a principal 4-electron transfer pathway. The n = 3.97 is higher than already reported on various shape controlled Cu 2 O nanostructures (Cu 2 O-70 ( n = 3.74); Cu 2 O-50 ( n = 3.22) and Cu 2 O-20 ( n = 2.04)) [ 65 ]. These are confirmed that the Cu@Cu 2 O core-shell nanocatalyst has direct 4-electron transfer pathway in ORR due to the synergistic morphological effects of a core-shell nanostructure, well dispersed Cu 2 O and the high, strong adsorption of O 2 on Cu@Cu 2 O surfaces.…”
Section: Resultsmentioning
confidence: 69%
“…The electron transfer number of Cu@Cu 2 O core-shell nanocatalyst estimated from the slope of the K–L plots is averagely 3.97 at 0.45–0.7 V, suggested a principal 4-electron transfer pathway. The n = 3.97 is higher than already reported on various shape controlled Cu 2 O nanostructures (Cu 2 O-70 ( n = 3.74); Cu 2 O-50 ( n = 3.22) and Cu 2 O-20 ( n = 2.04)) [ 65 ]. These are confirmed that the Cu@Cu 2 O core-shell nanocatalyst has direct 4-electron transfer pathway in ORR due to the synergistic morphological effects of a core-shell nanostructure, well dispersed Cu 2 O and the high, strong adsorption of O 2 on Cu@Cu 2 O surfaces.…”
Section: Resultsmentioning
confidence: 69%
“…Cu 2 O is a 3d transition metal oxide with intrinsic properties, and moreover, it is earth abundant and nontoxic, which makes it environmentally friendly as an excellent alternative material for different catalytic applications including photocatalytic hydrogen production, electrocatalytic determination, electrocatalytic CO 2 reduction, electrocatalytic OER and ORR . In spite of growing numbers of studies regarding the application and preparation of Cu 2 O, its electrochemical properties as catalysts for the HER have attracted less attention.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, by comparing the optical roughness curve (Figure ) and SEM Images (Figure ), it seems that by increasing the bath temperature, the surface roughness is increased gradually, as more complicated hierarchical structures appear This might be attributed to the acceleration of the copper ions towards cathode by increasing the bath temperature ,. However, further increasing of the temperature and approaching to the boiling point of the solvent (ultra‐pure water with the boiling temperature around 100 °C) led to disturbance in the ion transfer toward the cathode and consequently destruction of the deposited layer due to increasing of the random motion of the ions in the electrolyte ,. Thereupon, the deposition is impossible above the 80 °C.…”
Section: Discussionmentioning
confidence: 91%
“…Additionally, as it is already known, the bath temperature also affects ions velocity in the electrolyte ,. Increasing the ion velocity may strengthen coating of the layer.…”
Section: Introductionmentioning
confidence: 99%